Principles of International Justice under the Statute of the International Court of Justice and the ICCPR: Can they be Applied to Criminal Sanctions? - Wahyuni, Irma; Moenta, Andi Pangerang; Naswar, Naswar (Uti Possidetis: Journal of International Law, 2026)
Background The restriction of criminal sanctions in regional regulations  to fines as mandated by Indonesia's new Criminal Code raises crucial questions regarding their alignment with international standards of justice. As a state bound by the International Covenant on Civil and Political Rights (ICCPR) and the general principles of law enshrined in the Statute of the International Court of Justice (ICJ), Indonesia is obligated to ensure that all domestic legal instruments, including Regional Regulations, uphold principles of justice. Methodology: This normative study employs philosophical, statutory, comparative, and conceptual approaches. Primary and secondary legal materials including international instruments (ICJ Statute, ICCPR, UDHR) and interviews with international law experts were analyzed qualitatively. A comparative study was conducted regarding fine systems and public participation practices in the United Kingdom, Finland, Brazil, the Netherlands, and Japan. Objectives: To assess the compliance of criminal sanctions in Indonesian Regional Regulations with international legal principles of justice and to formulate necessary legal and institutional reforms. Findings: The absence of clear parameters for determining criminal sanctions in Regional Regulations leads to disparities, disproportionality, and legal uncertainty, potentially violating the principles of equality before the law and non-discrimination as set forth in the ICCPR and UDHR. To align with international standards, three essential reforms are required: (1) the formulation of national guidelines containing measurable criminalization parameters; (2) the institutionalization of meaningful public participation in the drafting of Regional Regulations; and (3) the affirmation of criminal sanctions as an ultimum remedium. Originality/Novelty: This study offers a multidimensional framework that evaluates Indonesian regional criminal sanctions through the lens of international law, bridges decentralization policies with global human rights obligations, and provides a model for harmonizing regional autonomy with international justice